# x²+12x+19 factorize (maths) pls answer fast urgent

## Answers

**Answer:**

x^2+12×+19=0

(0)^2+12(0)+19=0

0+0+19=0

0+19=0

=-19

**Step-by-step explanation:**

Hope u like my Answer and Mark me as Brainliest

**Answer:**

Simplifying

x2 + 12x + 19 = 0

Reorder the terms:

19 + 12x + x2 = 0

Solving

19 + 12x + x2 = 0

Solving for variable 'x'.

Begin completing the square.

Move the constant term to the right:

Add '-19' to each side of the equation.

19 + 12x + -19 + x2 = 0 + -19

Reorder the terms:

19 + -19 + 12x + x2 = 0 + -19

Combine like terms: 19 + -19 = 0

0 + 12x + x2 = 0 + -19

12x + x2 = 0 + -19

Combine like terms: 0 + -19 = -19

12x + x2 = -19

The x term is 12x. Take half its coefficient (6).

Square it (36) and add it to both sides.

Add '36' to each side of the equation.

12x + 36 + x2 = -19 + 36

Reorder the terms:

36 + 12x + x2 = -19 + 36

Combine like terms: -19 + 36 = 17

36 + 12x + x2 = 17

Factor a perfect square on the left side:

(x + 6)(x + 6) = 17

Calculate the square root of the right side: 4.123105626

Break this problem into two subproblems by setting

(x + 6) equal to 4.123105626 and -4.123105626.

Subproblem 1

x + 6 = 4.123105626

Simplifying

x + 6 = 4.123105626

Reorder the terms:

6 + x = 4.123105626

Solving

6 + x = 4.123105626

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.

6 + -6 + x = 4.123105626 + -6

Combine like terms: 6 + -6 = 0

0 + x = 4.123105626 + -6

x = 4.123105626 + -6

Combine like terms: 4.123105626 + -6 = -1.876894374

x = -1.876894374

Simplifying

x = -1.876894374

Subproblem 2

x + 6 = -4.123105626

Simplifying

x + 6 = -4.123105626

Reorder the terms:

6 + x = -4.123105626

Solving

6 + x = -4.123105626

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.

6 + -6 + x = -4.123105626 + -6

Combine like terms: 6 + -6 = 0

0 + x = -4.123105626 + -6

x = -4.123105626 + -6

Combine like terms: -4.123105626 + -6 = -10.123105626

x = -10.123105626

Simplifying

x = -10.123105626

Solution

The solution to the problem is based on the solutions

from the subproblems.

x = {-1.876894374, -10.123105626}